Aortic valve Libman-Sacks endocarditis with aortic root and coronary ostium involvement – A case report - Michele D’Alonzo; Eric Bergoend; Cyrus Moini; Antonio Fiore (Frontiers in Cardiovascular Medicine, 2026)
Background Libman-Sacks (LS) endocarditis, a nonbacterial thrombotic endocarditis, is the most frequent cardiac manifestation of systemic lupus erythematosus (SLE), particularly when associated with antiphospholipid syndrome (APS). It usually involves the mitral valve and is often clinically silent. Case summary We present a 25-year-old woman with SLE and APS who developed acute hemodynamic deterioration. Urgent surgery revealed a large endocarditic mass arising from the aortic valve leaflet, extending to the aortic root and obstructing the right coronary ostium. Resection and valve replacement were performed successfully. Discussion Unlike typical LS endocarditis, which manifests as mild valvular lesions, this case demonstrates rare aortic root involvement with coronary ostial obstruction. A review of the literature confirms that such an extension has not been previously reported, underscoring the heterogeneous and potentially life-threatening nature of LS endocarditis. Take home messages LS endocarditis can present atypically. Recognition of unusual patterns is critical for timely intervention.